Time from partitions to independence in the biographies of Suwałki priests Witold Balukiewicz (1891-1971) and Julian Łosiewski (1891-1961) – part 1 - Guzewicz, Wojciech; Moszczyński, Leszek (Studia Teologiczne Białystok Drohiczyn Łomża, 2023)
In the first part of the article, after a brief introduction the events taking place in the Polish-Lithuanian Commonwealth and later in the Suwalki Governorate from 1874 to 1915 are shown. The story of Olita (lit. Alytus), the hometown of Witold Balukiewicz and Julian Łosiewski, is outlined as well as their education in schools and later work in a pharmacy in Moscow. This part ends with a chapter devoted to their teaching at the Sejny Seminary, ending with the priestly ordination. In the background, the emerging Polish-Lithuanian conflict can be seen, related to the use of mother tongue in the church and the seminary.